Strengthening the Value of Religious Moderation Based on Local Wisdom at Islamic Basic Education Institutions in Kediri - Rahman, Marita Lailia (Proceedings of Annual Conference for Muslim Scholars, 2023)
Local wisdom in each region can be a source of strength to strengthen religious moderation. The values of local wisdom must be strengthened again in Islamic educational institutions in order to form students who have a high sense of humanity and form a generation that respects each other and lives in harmony. MIN 2 Doko Kediri is one of the Madrasah Ibtidaiyah Negeri that has implemented the value of local wisdom of religious moderation in programs and activities carried out in Madrasah. The purpose of this study is to describe the values of religious moderation reflected in local wisdom in MIN 2 Doko Kediri. This research method is qualitative, interview data collection techniques, observation and documentation. The results and discussion will discuss the strengthening of the value of religious moderation based on local wisdom in Madrasah. The conclusion in this study is that there are four strengthening values of religious moderation which are reflected in the attitudes of tolerance, love of the motherland, love of culture, and love of peace formed in programs and activities in Madrasah.